The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1590/1806-9282.62.08.721
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous intracranial epidural hematoma during rivaroxaban treatment

Abstract: According to our research, this is the first case described in the literature of spontaneous intracranial epidural hematoma secondary to the use of Xarelto ® . Spontaneous intracranial epidural hematomas are rarely described in the literature. They are associated with infectious diseases of the skull, coagulation disorders, vascular malformations of the dura mater and metastasis to the skull. Long-term post-marketing monitoring and independent reports will probably detect the full spectrum of hemorrhagic compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 15 publications
1
8
0
1
Order By: Relevance
“…Ruschel et al (2016) reported the first case of spontaneous intracranial epidural haematoma in a young patient on Rivaroxaban regime without any other medical co-morbidities. [16] There are increasing reports of bleeding and haemorrhagic complications in the elderly population on anti-coagulation medicines. Therefore, clinicians must be vigilant when prescribing the novel/newer or direct oral anticoagulants (NOAC or DOAC) such as Rivaroxaban, Apixaban and Dabigatran.…”
Section: Discussionmentioning
confidence: 99%
“…Ruschel et al (2016) reported the first case of spontaneous intracranial epidural haematoma in a young patient on Rivaroxaban regime without any other medical co-morbidities. [16] There are increasing reports of bleeding and haemorrhagic complications in the elderly population on anti-coagulation medicines. Therefore, clinicians must be vigilant when prescribing the novel/newer or direct oral anticoagulants (NOAC or DOAC) such as Rivaroxaban, Apixaban and Dabigatran.…”
Section: Discussionmentioning
confidence: 99%
“…However, spontaneous nontraumatic extradural hematomas are very rare and mostly occur due to vascular malformations,[12] sickle cell disease,[13] metastasis to the skull,[4] infectious diseases of the skull,[12] coagulation disorders,[14] and use of anticoagulants. [15]…”
Section: Discussionmentioning
confidence: 99%
“…However, spontaneous nontraumatic extradural hematomas are very rare and mostly occur due to vascular malformations, [12] sickle cell disease, [13] metastasis to the skull, [4] infectious diseases of the skull, [12] coagulation disorders, [14] and use of anticoagulants. [15] When hypofibrinogenemia is the cause of an intracranial extradural hematoma, time is the essence of successful therapy. Early identification and treatment is paramount to save the patient.…”
Section: Discussionmentioning
confidence: 99%
“…In the study it was reported that the active principle Rivaroxabana caused a secondary spontaneous epidural hematoma in the patient. (RUSCHEL et al, 2016). 6 According to Table 1, non-traumatic epidural hemorrhages are the cause of death in 67 people from Chen et al (2018) 8 in your study described that the prognosis of EDH is excellent if early diagnosis is made in conjunction with a surgical decompression.…”
Section: Physiopathologymentioning
confidence: 99%
“…(RUSCHEL et al, 2016). 6 According to Table 1, non-traumatic epidural hemorrhages are the cause of death in 67 people from Chen et al (2018) 8 in your study described that the prognosis of EDH is excellent if early diagnosis is made in conjunction with a surgical decompression. Besides, the authors highlight that spontaneous EDH is a rare condition, which may have some unusual triggers such as crying and hyperventilation, the presence of headaches with signs of increased intracranial pressure preceded by hyperventilation suggests that computed tomography examination should be done.…”
Section: Physiopathologymentioning
confidence: 99%